Genomic profiling of Elizabethkingia anophelis clinical isolates from a Shanghai hospital: phylogenetic divergence coexists with heterogeneous antibiotic resistance and virulence determinants - Xiong, Jiasheng; Han, Tiantian; Hu, Jingjing; Wu, Yitian; Huang, Xiaoyan; Yang, Dianyu; Hou, Weiwei; Lin, Yan (Frontiers in Microbiology, 2026)
IntroductionElizabethkingia anophelis (E. anophelis) has emerged as a multidrug-resistant pathogen with limited therapeutic options. This study aimed to characterize antimicrobial resistance mechanisms and virulence determinants in six clinical isolates from Shanghai, China, to inform evidence-based treatment strategies.MethodsSix strains were isolated from hospitalized patients (five community-acquired, one healthcare-associated) between September–November 2023. Antimicrobial susceptibility testing followed CLSI M100 guidelines. Whole-genome sequencing employed hybrid Illumina/PacBio approaches. Phylogenetic relationships were determined through 16S rRNA gene sequence analysis using the Neighbor-Joining method. Antimicrobial resistance genes and virulence factors were annotated using the Comprehensive Antibiotic Resistance Database (CARD) and Virulence Factor Database (VFDB), with relative gene abundance quantified via a TPM-like (transcripts per million-like) method.ResultsAll isolates exhibited resistance to β-lactams, fluoroquinolones, carbapenems, and aminoglycosides, but retained minocycline susceptibility (MIC ≤1 μg/mL). Phylogenetic analysis revealed two distinct clusters: Cluster I (EA1, EA3, EA6) aligning with East/Southeast Asian isolates, and Cluster II (EA2, EA4, EA5) showing diverse geographic affinities. Five core resistance mechanisms were identified: antibiotic efflux, antibiotic target alteration, antibiotic inactivation, antibiotic target replacement, and reduced permeability to antibiotics. Virulence determinants included bacterial movement, exotoxin production, biofilm formation, immune regulation, and effector delivery systems. Strain EA5 exhibited unique signatures, including absence of cesH, unique sigE expression, elevated AAC(6′)-Iad/aadS and reduced qacL/OmpA.ConclusionThis study reveals phylogenetically divergent E. anophelis lineages in Shanghai with extensive multidrug resistance but preserved minocycline susceptibility. Findings support minocycline-based therapy, enhanced diagnostics, and regional surveillance networks for strain monitoring.